Monitoring Public Company Rankings for Investment Decisions: Are They Undervalued or Overvalued? - Wu, Wei-Wen (2013)
This study proposes a novel framework to monitor the rankings of public companies that are released periodically by worldwide business organizations. With different ranking rationales and diverse indicators, the released reports may not be comparable or suited to investment objectives. Therefore, this study introduces the DuPont model to derive well-recognized common investment indicators and then employs the data envelopment analysis (DEA) ranking method and the grey entropy (GE) ranking method to re-rank the listed companies. Both DEA and GE re-rankings are compared with the released rankings to generate a map of the DEA-gap versus the GE-gap to advise stock investors of undervalued or overvalued companies. As a demonstration, the proposed framework is applied to the case of Taiwan Info Tech 100 released by Business Next. It is thought that continual monitoring of public company rankings may promote business opportunities in the long run; hence, application of the proposed framework to develop favorable business models is further addressed in this study.